Validation of the rapid test Carestart(tm) G6PD among malaria vivax-infected subjects in the Brazilian Amazon - Brito, Marcelo Augusto Mota; Peixoto, Henry Maia; Almeida, Anne Cristine Gomes de; Oliveira, Maria Regina Fernandes de; Romero, Gustavo Adolfo Sierra; Moura-Neto, José Pereira; Singh, Nakul; Monteiro, Wuelton Marcelo; Lacerda, Marcus Vinícius Guimarães de (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
In the Brazilian Amazon, malaria infections are primarily caused by Plasmodium vivax. The only drug that kills the hypnozoite form of P. vivax is primaquine, thereby preventing relapse. However, treating glucose-6-phosphate dehydrogenase (G6PD)-deficient individuals with primaquine can lead to severe hemolysis. G6PD deficiency (G6PDd) affects approximately 400 million people worldwide, most of whom live in malaria-endemic areas. Therefore, clinicians need tools that can easily and reliably identify individuals with G6PDd. This study estimated the accuracy of the Carestart(tm) G6PD rapid test (Access Bio) in the diagnosis of G6PDd in male participants with and without P. vivax acute malaria. Male participants were recruited in Manaus. Malaria diagnosis was determined by thick blood smear. G6PD quantitative analysis was performed spectro photometrically at a wave length of 340nm. The Carestart(tm) G6PD test was performed using venous blood. Genotyping was performed for individuals whose samples had an enzyme activity less than 70% of the normal value. Six hundred and seventy-four male participants were included in this study, of whom 320 had a diagnosis of P. vivax malaria. In individuals with enzyme activity lower than 30% (n=13), the sensitivity, specificity, positive predictive value, and negative predictive value of the Carestart(tm) G6PD test were as follows: 61.5% (95%CI: 35.5%-82.3%), 98.3% (95%CI: 97.0%-99.1%), 42.1% (95%CI: 23.1%-63.7%), and 99.2% (95%CI: 98.2%-82.3%), 98.3% (95%CI: 97.0%-99.1%), 42.1% (95%CI: 23.1%-63.7%), and 99.2% (95%CI: 98.2%-99.7%), respectively. Increases in sensitivity were observed when increasing the cut-off value. Despite low sensitivity, Carestart(tm) G6PD remains a good alternative for rapid diagnosis of G6PDd in malaria-endemic regions.